Prevalence of fibrinous pericarditis in heavy pigs (170 kg) and its association with other pluck lesions at slaughter inspection. (July 2021) - Bottacini, M.; Scollo, A.; Contiero, B.; Mazzoni, C.; Pace, V.; Gottardo, F.
Highlights: Italian pigs slaughtered at 170 kg had a 5.66% prevalence of fibrinous pericarditis. Fibrinous pericarditis was closely linked to the presence of pleuritis. High batch pericarditis rates were linked with higher pneumonia and pleurisy rates. Farm of origin accounted for 17.7% batch variation in prevalence of pericarditis. Abstract: This study determined the prevalence of fibrinous pericarditis and its correlation with other pluck lesions in 658 batches of pigs from 236 intensive farms located in Northern Italy over a 12-month period. All pigs were slaughtered at 170 kg, and a total 57, 943 plucks (approximately 90 pigs/batch) were individually assessed for the presence of fibrinous pericarditis, pneumonia, pleuritis, and liver milk spots. There was no seasonal variation in the prevalence of plucks with fibrinous pericarditis and annual mean prevalence was 5.6% (range, 0–26.3% at batch level; median, 4.71%). Farm of origin, evaluated as a random effect, accounted for 17.7% batch variation. Batches with a high prevalence of fibrinous pericarditis (≥7.7%) had higher prevalences of pleural, pulmonary, and liver lesions than those with low-middle prevalence of pericarditis; high prevalence of pericarditis was predictive of pluck lesions ( P < 0.001). There was a highly significant association between fibrinous pericarditis and severe pleuritis, and 55% of plucks with the highest score for pleuritis also had ongoing fibrinous pericarditis, with a positive correlation at batch level ( r 2 = 0.52; P < 0.001). The co-existence of pericarditis and pleuritis (73.5% of all pericarditis cases) suggests that pleuritis plays a role in the pathogenesis of pericarditis. Based on the prevalence fibrinous pericarditis, and the role of pleuritis as a potential comorbidity, abattoir data on pluck lesions with accompanying farm history, could aid the interpretation and management of on-farm health problems, and inform diagnostic protocols.